Umbilical Cord Blood: A Trustworthy Source of Multipotent Stem Cells for Regenerative Medicine - Tang-Her Jaing M.D. (Cell Transplantation, 2014)
It is conservatively estimated that one in three individuals in the US might benefit from regenerative medicine therapy. However, the relation of embryonic stem cells (ESCs) to human blastocysts always stirs ethical, political, moral, and emotional debate over their use in research. Thus, for the reasonably foreseeable future, the march of regenerative medicine to the clinic will depend upon the development of non-ESC therapies. Current sources of non-ESCs easily available in large numbers can be found in the bone marrow, adipose tissue, and umbilical cord blood (UCB). UCB provides an immune-compatible source of stem cells for regenerative medicine. Owing to inconsistent results, it is certainly an important and clinically relevant question whether UCB will prove to be therapeutically effective. This review will show that UCB contains multiple populations of multipotent stem cells, capable of giving rise to hematopoietic, epithelial, endothelial, and neural tissues both in vitro and in vivo. Here we raise the possibility that due to unique immunological properties of both the stem cell and non-stem cell components of cord blood, it may be possible to utilize allogeneic cells for regenerative applications without needing to influence or compromise the recipient immune system.